Biotechnology of Plastic Waste Degradation, Recycling, and Valorization: Current Advances and Future Perspectives. Issue 19 (14th September 2021) - Qin, Zi‐Hao; Mou, Jin‐Hua; Chao, Christopher Yu Huang; Chopra, Shauhrat Singh; Daoud, Walid; Leu, Shao‐yuan; Ning, Zhi; Tso, Chi Yan; Chan, Chak Keung; Tang, Shixing; Hathi, Zubeen Jyotiwadan; Haque, Md Ariful; et al.
Abstract: Invited for this month′s cover is the collaborative group of Dr. Carol Sze Ki Lin and Dr. Xiang Wang. The image illustrates the biodegradation of plastics and the potential for plastic waste recycling and valorization to address the plastic waste dilemma. The Minireview itself is available at 10.1002/cssc.202100752 . Abstract : "…plastic leads to severe pollution that cannot be easily treated." This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202100752 . View the Front Cover here: 10.1002/cssc.202101826 .